A systematic comparison of single-crystal and polycrystalline models in predicting high-entropy alloys deformation behavior - Wang, Peng wei; Li, Ming fei; Wang, Yi jie; Ge, Chuan Nan; Lei, Cheng Long; Choo, Wei Chong (Elsevier, 2025)
As high entropy alloys (HEAs) emerge as structural materials, clarifying their deformation mechanisms is essential. Using molecular dynamics (MD) simulations, this study compares tensile behavior of single-crystal and polycrystalline FeNiCrCuAl HEAs. Both exhibit stable atomic structures, and polycrystalline HEAs show broader and lower radial distribution function peaks due to grain boundary distortions. Although their elastic responses are similar, the single-crystal HEA achieves higher peak stress with sharp drops, whereas the polycrystalline model demonstrates lower strength but stable plasticity. Phase transformations occur in both, with HCP forming earlier in polycrystalline. Dislocation evolution also differs because the polycrystalline model has a higher initial dislocation density, while single crystals rapidly accumulate dislocations that lead to strain localization. Shear bands align with crystallographic orientations in single crystals but nucleate at grain boundaries in polycrystalline. These findings highlight the critical role of grain boundaries in governing HEA deformation and provide guidance for optimizing mechanical performance.